Software Testing for Microservices - Laura Mamani, Cesar Adolfo (2023)
Microservices have emerged as an architectural style that offers many advantages, but also poses challenges. One of these challenges revolves around testing, as an application may have hundreds or thousands of services running together, each requiring testing as they evolve. To overcome this challenge, automation takes on a key role, and along with it, the use of efficient and effective testing tools.